Screening, Identification and Enzymatic Properties of Myrosinase-Producing Sphingobacterium RJ35 - ZHU Rongjun, FANG Yaowei, YE Qinwen, HOU Xiaoyue, YANG Guang, YANG Yunqiong, LIU Shu (Shipin Kexue, 2023)
In this study, a myrosinase-producing strain named RJ35 was isolated from a rapeseed field soil, and it was identified by morphological and molecular biological methods. The myrosinase produced by strain RJ35 was purified by sequential ultrafiltration and gel filtration chromatography and its enzymatic properties were studied. Strain RJ35 was assigned to the genus Sphingobacter. The molecular mass of the myrosinase was about 100 kDa. The optimum pH and temperature of the myrosinase were 7.5 and 40 ℃, respectively. Moreover, metal ions had no significant activating effect on the myrosinase. The results of high performance liquid chromatography (HPLC) showed that this enzyme could hydrolyze radish seed extract to produce sulforaphane. Hydrolysis for 30 min under the optimum conditions resulted in a yield of sulforaphane of 5.95 mg/g (radish seed). These research results may lay an experimental foundation for the development of microbial myrosinase.